The AEC and a Technology-Driven Industrial Catch-Up: Three ASEAN Country Cases - Purbantina, Adiasri Putri (Global and Policy Journal of International Relations, 2019)
ABSTRACTThere is a growing consensus that effective Science, Technology, and Innovation (STI) policies, aimed at supporting long-term national structural transformation, are a crucial element in helping latecomer countries escape from the middle-income trap. Citing cases of Northeast Asian catch-up and Latin American middle-income traps, scholars emphasize that the key to catch-up is a triple-helix coordination that is used to transform foreign technology into indigenous technological capabilities. Thus, ideally, the expansion of the global production network, as promoted by the ASEAN Economic Community (AEC), provides opportunities for middle-income ASEAN countries to implement this technology-driven industrial catch-up strategy. This paper investigates three middle-income ASEAN countries (Malaysia, Thailand, and Indonesia) to argue that the AEC, as an open market-led economic regionalism scheme, does not have the ability to create a strong sense of urgency on the part of national governments to alter their national STI policy directions. As resource-abundant countries, Malaysia, Thailand, and Indonesia have yet to find any urgent need to prioritize the upgrading of indigenous manufacturing over natural resource-based technological developments. For these three countries, the AEC amplifies the need to compete against other ASEAN member countries instead pushing them to pursue industrial catch-up collectively.Keywords: economic regionalism, STI, industrial catch-up, ASEAN DOI : https://doi.org/10.33005/jgp.v7i02.1832